Marine Bioinvasions: Patterns, Processes and Perspectives - Pederson, Judith (Springer Netherlands : Imprint: Springer, 2003)
As the global rate of marine introductions increases, exotic species exert greater economic and ecological impacts, affecting ecosystems and human health. The complexity of marine ecosystems challenges our ability to find easy solutions to prevention, management, and control of introductions. This book highlights issues of timely importance in marine bioinvasion science. Selected topics explore the potential evolutionary consequences and ecological impacts of introduced organisms, examine the feasibility of biological control, and describe patterns of introduction. These papers were presented at the Second International Conference on Marine Bioinvasions, which featured new marine invasion research from around the world. These papers should be of interest to scientists, students, and managers with an interest in marine bioinvasions and the application of knowledge to management concerns.